Úpravy výrazů 2

Zjednodušte:

  1. \displaystyle \left[1-a^2(1+a^2)^{-1} \right]^{-1}=
  2. \displaystyle \left[1-(1-3x)^{-1}\right]\cdot\left[1-(3x+1)^{-1} \right]=
  3.       \displaystyle \left[a(a-2)^{-1}-a(a+2)^{-1}\right]:\frac{4}{a^3-2a^2}=
  4.       \displaystyle \left[(c^2-1)^{-1}+1\right]^{-2}:(1-c^{-4})=
  5.       \displaystyle \left[\frac{x^2-9}{x+1}:\frac{x-3}{1-x^2} \right]^{-1}=
  6.       \displaystyle \left(a^{-2}+b^{-2} \right)^{-1}\cdot\left(\frac{ab}{a^2+b^2}\right)^{-2}=
  7.       \displaystyle \left(z+2\right)^{-1}\cdot\left(z-4z^{-1}\right):(4-z^2)=
  8.       \displaystyle \left(p^{-1}-q^{-1}\right):(p^2-pq)=
  9.       \displaystyle \left(\frac{z^2-z}{z^2-9}\right)^{-1}:\frac{z^2-3z}{z-1}=
  10.       \displaystyle \left[(1-v)^{-1}+(1+v)^{-1}\right]^{-1}=
  11.       \displaystyle \frac{(x-1)^{-1}}{x^{-3}}+(1-x)^{-1}=
  12.       \displaystyle (u^{-2}+v^{-2})(u^2+v^2)^{-1}+2(u^2v^2)^{-1}=
  13.       \displaystyle \left(\frac{n^2}{n^2-4}+\frac{n+3}{n+2}-\frac{n-3}{n-2}\right)\left(1-\frac{2}{n}\right)=
  14.       \displaystyle \left[\left(\frac{a+1}{2}\right)^{\frac{1}{2}}+\left(\frac{a-1}{2}\right)^{\frac{1}{2}} \right]^2=

Napsat komentář

Vaše emailová adresa nebude zveřejněna. Vyžadované informace jsou označeny *